GENETIC DIVERSITY OF FRESHWATER MURREL, CHANNA PUNCTATUS (BLOCH, 1793) - KASHYAP, ANKUR; AWASTHI, MADHU; SINGH, MINAKSHI; SERAJUDDIN, MOHAMMAD (Journal of the Inland Fisheries Society of India, 2021)
Genetic variation of freshwater murrel, Channa punctatus populations was analyzed using random amplified polymorphic DNA-polymerase chain reaction (RAPD-PCR). 50 loci were amplified out of which 44 (88%) and 6 (12%) were polymorphic and monomorphic respectively indicating high percentage of polymorphism. Highest polymorphism with 35 (70%) polymorphic loci and maximum gene diversity of 0.2031 was found in the river Gomti, whereas polymorphic loci in the population from pond of Kolkata and Malihabad was 26 (52%) and 19 (38%) respectively. The dendogram discriminated the three populations of C. punctatus on the basis of genetic distance.Key words : Channa punctatus, genetic diversity, river Gomti